Electron Inflow Velocities and Reconnection Rates at Earth's Magnetopause and Magnetosheath. Issue 17 (31st August 2020) - Burch, J. L.; Webster, J. M.; Hesse, M.; Genestreti, K. J.; Denton, R. E.; Phan, T. D.; Hasegawa, H.; Cassak, P. A.; Torbert, R. B.; Giles, B. L.; Gershman, D. J.; Ergun, R. E.; et al.
Abstract: Electron inflow and outflow velocities during magnetic reconnection at and near the dayside magnetopause are measured using satellites from NASA's Magnetospheric Multiscale (MMS) mission. A case study is examined in detail, and three other events with similar behavior are shown, with one of them being a recently published electron‐only reconnection event in the magnetosheath. The measured inflow speeds of 200–400 km/s imply dimensionless reconnection rates of 0.05–0.25 when normalized to the relevant electron Alfvén speed, which are within the range of expectations. The outflow speeds are about 1.5–3 times the inflow speeds, which is consistent with theoretical predictions of the aspect ratio of the inner electron diffusion region. A reconnection rate of 0.04 ± 25% was obtained for the case study event using the reconnection electric field as compared to the 0.12 ± 20% rate determined from the inflow velocity. Key Points: Electron inflow velocities are determined for reconnection at the magnetopause and in the magnetosheath For four events inflow velocities of 200–400 km/s imply normalized reconnection rates of 0.05–0.25 Reconnection rates using electron inflow velocities (0.12) and the reconnection electric field (0.04) are compared for one event Plain Language Summary: When the solar wind impacts the Earth's magnetosphere, an explosive energy conversion process called magnetic reconnection opens the door for solar wind energy to enter the magnetosphere by interconnection of the magnetic fields of the solar wind and of Earth. In this process, magnetic energy is converted to charged‐particle energy. Magnetic reconnection is fairly well understood at large scales and even down to the ion scale. However, the breaking and linking of field lines and the acceleration of electrons occur at much smaller scales, which are only recently being accessed by the NASA Magnetospheric Multiscale mission. This paper analyzes the speed at which electrons flow into and out of reconnection sites. The inflow speeds are crucial because they provide a measurement of the rate at which reconnection proceeds.